2011
DOI: 10.22456/1982-8918.20590
|View full text |Cite
|
Sign up to set email alerts
|

O Corpo Negro E Os Preconceitos Impregnados Na Cultura: Uma Análise Dos Estereótipos Raciais Presentes Na Sociedade Brasileira a Partir Do Futebol

Abstract: Os autores analisaram os signif icados dos estereótipos sobre a "raça negra" através do futebol. Simbolizados através das imagens de "macacos" ou inscritas no "mundo natural/animal", quais sentidos assumem os estereótipos construídos sobre a "raça negra" que têm sido acionados através do futebol brasileiro? Para tanto, observaram as ofensas que ocorreram nos estádios no hiato de 2005 até 2011 e concluíram que o fato dessas representações terem emergido num momento de conflito revela que "raça" é uma moeda acio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
1
0
2
Order By: Relevance
“…But, Emanoel Araújo, without losing critical dimension, closes the text of the exhibition (Figure 6) highlighting the manifestations of racist injuries still present in today's soccer, and questions whether soccer "could really be" an expression and access to Brazilian culture and a space for "the ascension of the black sportsman". The curator here reported that black players were called monkeys in different audiences around the world (Abrahão & Soares, 2011). Note that the museum, when exhibiting soccer and the great afrodescendent players, chose to reconcile the vision of struggle, integration and heroization of blacks in soccer, and to provoke criticism of racism still present in soccer and in society.…”
Section: Friedenreich In the Sao Paulo Museumsmentioning
confidence: 97%
“…But, Emanoel Araújo, without losing critical dimension, closes the text of the exhibition (Figure 6) highlighting the manifestations of racist injuries still present in today's soccer, and questions whether soccer "could really be" an expression and access to Brazilian culture and a space for "the ascension of the black sportsman". The curator here reported that black players were called monkeys in different audiences around the world (Abrahão & Soares, 2011). Note that the museum, when exhibiting soccer and the great afrodescendent players, chose to reconcile the vision of struggle, integration and heroization of blacks in soccer, and to provoke criticism of racism still present in soccer and in society.…”
Section: Friedenreich In the Sao Paulo Museumsmentioning
confidence: 97%
“…28 Sendo o preconceito uma opinião pré-estabelecida ou um julgamento prévio, impostos pelo meio, que regula as relações entre as pessoas, bem como entre as sociedades. 29 Os estereótipos, "imagens, explicações, ideias ou sistemas de ideias que, generalizando o resultado de experiências parciais e limitadas, caracterizam o conteúdo alógico de nossos pensamentos, julgamentos e ações" 30 . Ainda, Munanga, afirma que a "discriminação é a passagem de uma simples atitude preconceituosa, a uma ação observável e às vezes mensurável" 31 .…”
Section: Raça Racismo E Etniaunclassified
“…Depreende-se daí uma das estratégias utilizadas para a reprodução "informal" dos preconceitos, uma das principais características do "racismo à brasileira. (ABRAHÃO;SOARES, 2011, p. 277-278).…”
unclassified